Determination of the impact of infant and young child feeding counselling services on the knowledge of mother-children dyads less than two years - Moras, Karen Janice; Benakappa, Asha D.; Belavadi, Gangadhar (International Journal of Contemporary Pediatrics, 2021)
Background: Optimum infant and young child feeding (IYCF) practices are essential for adequate growth and development of infants and children. Malnutrition in children occurs almost entirely during the first two years of life, is virtually irreversible after that. Despite the IYCF guidelines, there is no consistent literature on the prevalence of existing IYCF practices and impact of optimum IYCF practices. This study was conducted to estimate the prevalence of existing IYCF practices and to determine the impact of IYCF counseling in children less than 2 years. Methods: A cross-sectional before and after study was done in mother-children dyads (aged 0-24 months). All 125 mother-children dyads were interviewed using prevalidated IYCF questionnaire after obtaining informed consent. The pre-counseling knowledge of mothers, on existing IYCF practices were analyzed using IYCF core and optional indicators. At 6 weeks, the post-counselling knowledge of the mothers was assessed using the same core and optional indicators. Results: Exclusive breastfeeding was seen in 18 of 43 (41.8%) mothers who showed statistically significant improvement to 40 (93%) (p<0.001) after counseling. Children ever breastfed were 62.4%. Predominat breastfeeding was observed in 24%. Initiation of complementary feeding at 6 months of age, improved significantly (p<0.001) post-counseling from 19 mothers (82.6%) to 23 mothers (100%). Minimum dietary diversity improved significantly post counseling, from 23 (28.7%) children to 70 children (87.5%) (p=0.03). Minimum meal frequency was only 22 (48.8%) in breastfed and 8 (22.9%) in non-breastfed children before counseling and improved to 40 (88.9%) in breastfed and 28 (80%) in non-breastfed children (p=0.04). The minimum acceptable diet was given to 2 (4.4%) children aged 6-23 months out of 45 in the breastfed group and on counseling, it improved to 37 (82.23%), which was statistically significant (p<0.001). Among the 35 non-breastfed children, with 2 children aged 6-23 months receiving minimally acceptable diet increased to 28 (80%) post counseling, which was found to be statistically significant (p<0.0001). A significant reduction in bottle feeding was observed from 52 (41.6%) mothers bottle feeding pre counseling, to 18 (1.4%) post counseling (p<0.001). Conclusions: The present study concludes that maternal education on IYCF practices improves their knowledge significantly irrespective of their socioeconomic and education status. Effective IYCF counselling services improve the growth and development of a child. IYCF counselling services provide a critical window of opportunity to tackle the malnutrition crisis and ensure and promote appropriate child growth and survival.